2007
DOI: 10.1080/03634520601009710
|View full text |Cite
|
Sign up to set email alerts
|

I'll See You On “Facebook”: The Effects of Computer-Mediated Teacher Self-Disclosure on Student Motivation, Affective Learning, and Classroom Climate

Abstract: informa que el(los) autor(es) ha(n) autorizado a usuarios internos y externos de la institución a consultar el contenido de este documento a través del Catálogo en línea de la Biblioteca y el Repositorio Institucional en la página Web de la Biblioteca, así como en las redes de información del país y del exterior con las cuales tenga convenio la Universidad de La Sabana.Se permite la consulta a los usuarios interesados en el contenido de este documento para todos los usos que tengan finalidad académica, nunca p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
411
1
25

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 771 publications
(488 citation statements)
references
References 40 publications
19
411
1
25
Order By: Relevance
“…Given the widespread popularity of ubiquitous SNTs (Brenner, 2012), many teachers and instructors have come to use these platforms to communicate with their students. SNT-based teacher-student communication complements and sometimes even replaces more traditional communication channels, such as faceto-face, email or school-supported learning management systems (LMSs) (e.g., Andersson, Hatakka, Grönlund, & Wiklund, 2014;Asterhan & Rosenberg, 2015;Mazer, Murphy, & Simonds, 2007;Schwarz & Caduri, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Given the widespread popularity of ubiquitous SNTs (Brenner, 2012), many teachers and instructors have come to use these platforms to communicate with their students. SNT-based teacher-student communication complements and sometimes even replaces more traditional communication channels, such as faceto-face, email or school-supported learning management systems (LMSs) (e.g., Andersson, Hatakka, Grönlund, & Wiklund, 2014;Asterhan & Rosenberg, 2015;Mazer, Murphy, & Simonds, 2007;Schwarz & Caduri, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Emerson Gomes Dos Santos e Rogério Scabim Morano O Facebook, por sua vez, pode ser usado para criar e promover conexões entre alunos e professores dentro de uma comunidade acadêmica (Mazer, Murphy & Simonds, 2007). Esse aumento na comunicação promovida pela rede social pode ter impacto positivo sobre as discussões da classe e incrementa a integração e o engajamento dos estudantes (Ross et al, 2009).…”
Section: Uso Do Facebook Na Educaçãounclassified
“…In their research on instructors' use of Facebook, Mazer et al (2007b) found that students perceived teachers who were highly self-disclosive on Facebook as being more credible than teachers who were less self-disclosive. Additionally, students who viewed instructors with high amounts of self-disclosure on Facebook reported higher levels of motivation, affective learning, and evaluated the classroom climate more positively than those who were exposed to a teacher who limited their disclosures on Facebook (Mazer et al, 2007a).…”
Section: Instructor's Credibility and Self-disclosurementioning
confidence: 99%
“…Indeed, some students may be hesitant to initiate communication with instructors outside of class (Kelly, Duran, & Zolten, 2001;Martin & Myers, 2006). Communication researchers have recently focused attention on how students and instructors communicate via technology (e.g., Johnson, 2011;Mazer, Murphy, & Simonds, 2007a, 2007b, and how forms of technology, such as Twitter, can serve as a form of informal communication with instructors. Thus, the current study examines Twitter as a mechanism of informal communication between instructor and student.…”
Section: Instructor Credibility and Technologymentioning
confidence: 99%
See 1 more Smart Citation